The Effect Of Velocity Based Resistance Training Towards Regional Training Camps Athletes In Koni Jambi - Endarman Saputra; zamzami (Cerdas Sifa Pendidikan, 2019)
Abstract The purpose of this study was to obtain information about the effect of Velocity Based Resistance Training towards Regional Training Camps Athletes in Koni Jambi. The research method used is the Experimental method. The population of the research was 12 athletes who joined in regional training camps in Koni Jambi, and made all of the samples population called total sampling. This research instrument is medicine ball throw test. This research was conducted for 6 months including preparation until reporting. The study used quasi-experimental research with One-Group Pre-Test Post-Test where there was 1 independent variable and 1 dependent variable. The sample will be tested then given treatment and after that will be tested again to find out the increase in results after being given treatment. The data retrieval technique uses medicine ball throw test. Kata Kunci: Velocity Based Resistance Training, Regional Training Camps Athletes